In search for support for the extension of copyright term under the Trans-Pacific Partnership Agreement: A preliminary study of the Malaysian music industry - Abdul Ghani Azmi, Ida Madieha; Alavi, Rokiah (Emerald, 2017)
Purpose – One of the binding commitments under the Trans-Pacific Partnership Agreement is the extension of the copyright term to 70 years after the death of the author. This paper reports the preliminary findings of a research on the potential impact of the extension of copyright term on the music industry in Malaysia. As Malaysia is a user and net importer of intellectual property, it is feared that extending the copyright term will likely impede incentives for the creation of new contents, increase the cost of licensing/ royalties, diminish the choice and creativity of film and music industry and increase royalty payments abroad. The purpose of this study is to determine whether the commercial lifespan of copyright works is long enough. Design/methodology/approach – Using a qualitative research method, in-depth interviews were carried out with key industry players between June and September 2015 to collect relevant information from the industry. The information obtained was analysed to gauge the market standing of the local music industry and how the proposed extension would bolster their financial and market power. The paper does not intend to explore the legal implications from the retrospective extension of copyright term and data on illegal use and piracy. The findings of the research will be purely drawn from the non-structured interviews and information gathered from respondents. Findings – The paper concludes that there is not enough evidence to support the notion that the copyright extension will be economically advantageous to the local music industry. Research limitations/implications – The feedback from the interviews, although cannot be generalised to be considered as representing the whole music industry in Malaysia, can nevertheless be taken as preliminary conclusions and an eye-opener to the quest for concrete support in the debate for the extension of the copyright term in Malaysia. The paper also does no explore the legal implications from the retrospective extension of copyright and data on illegal use and piracy. Practical implications – In conclusion, more studies need to be conducted to understand the dynamics and needs of the music market in Malaysia for the extension of the copyright term to be really beneficial to them. As this study is only conducted using a qualitative research method, using open-ended and in-depth interview techniques on a small group of respondents, there may be a need to embark on empirical research with proper execution of survey instruments to a larger group of respondents.